Efficacy and safety of rituximab-based chemoimmunotherapy in adult patients with Burkitt lymphoma in Korea - Min, Gi-June; Kim, Ka Young; Kim, Tong Yoon; Jeon, Young-Woo; Kim, Byung-Su; Yahng, Seung-Ah; Eom, Ki-Seong; Cho, Seok-Goo (Frontiers in Oncology, 2025)
BackgroundBurkitt lymphoma (BL), a rare, aggressive MYC-driven B-cell non-Hodgkin lymphoma (NHL), has endemic, sporadic, and immunodeficiency-associated variants. In Asia, BL accounts for 1–2% of lymphomas, with limited data available on adult outcomes. Although potentially curable, BL is associated with poor outcomes with low-intensity chemotherapy owing to rapid proliferation and chemoresistance. Therefore, high-intensity regimens including R-hyperCVAD/MC (Course A of rituximab, cyclophosphamide, doxorubicin, vincristine, and dexamethasone; Course B of rituximab, methotrexate, and cytarabine) have been commonly used; however, no optimal strategy has been established.MethodsThis retrospective study included 69 adult patients with BL (age >15 years) diagnosed between 2009 and 2023 using the WHO criteria. Most of the patients were administered R-hyperCVAD/MC, while rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) was administered to older patients or those with poor-performance-status to mitigate toxicity.ResultsThe median age of the patients was 55 years; 39.1% of the patients had Eastern Cooperative Oncology Group Performance Status (ECOG-PS) of 2–4, 62.3% had >1 extranodal site, 71.0% had stage IV, and 13.0% had central nervous system involvement. Furthermore, 13 (18.8%) patients were reclassified as BL after immunoglobulin heavy‐chain (IGH)/MYC detection. Overall, 52 patients were administered R-hyperCVAD/MC exclusively, 5 switched from R-CHOP, and 4 patients were primarily treated with R-CHOP owing to intolerance. At a median follow-up of 66.9 months, 5-year overall survival (OS) and event-free survival (EFS) were 69.5 and 65.2%, respectively and higher early mortality was observed in older patients (median survival: 3.9 months). Poor OS was associated with B-symptoms (hazard ratio [HR] 3.89, p = 0.003) and age ≥ 60 years (HR 2.54, p = 0.034); while poor EFS was associated with ECOG-PS 2–4 (HR 2.72, p = 0.024).ConclusionsOur study revealed that R-hyperCVAD/MC was effective but associated with high early mortality in older patients. Risk-adapted regimens and prognostic factors including age, B-symptoms, and ECOG-PS are crucial for optimizing treatment.